Evaluation of Molecular and Culture Method for Detection of Campylobacter, Salmonella, E. coli and Shigella in children infected with Diarrhea - Saife D. Al-Ahmer; Musa K. Al-Janabi; Iman M. Aufi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Acute diarrhea is the second most common cause of children deaths worldwide. Bacterial pathogens havebeen confirmed as the major cause of acute diarrhea among children. In this study, 100 stool samples wereinvestigated from pediatric children with acute diarrheal illness aged from 1 month to 5 years old. Bacterialinvestigated was performed for the common enteric pathogens: Campylobacter, Salmonella, Shigella, andDiarrheagenic Escherichia coli included Microscopy, culture and confirmatory identification by biochemicalreactions included API 20E system. Finally, the real time PCR investigated for these enteric bacteria. Theoverall prevalence of the pathogens for Campylobacter, Salmonella, Shigella and Diarrheagenic E. coli were9%, 8%, 3% and 14%, respectively. The results showed significant association of the clinical symptoms withShigella and Salmonella infection. The RT-PCR markedly improves the detection rates of bacterial stoolpathogens and offers culture methods.